COST ANALYSIS OF WATER PUMPING USING SOLAR ENERGY AND DIESEL IN DRIP IRRIGATION - Alves, Dinara Grasiela; Pinto, Marinaldo Ferreira; Damasceno, Ana Paula Alves Barreto; Grah, Vanessa de Fátima; Botrel, Tarlei Arriel (IRRIGA, 2014)
COST ANALYSIS OF WATER PUMPING USING SOLAR ENERGY AND DIESEL IN DRIP IRRIGATION DINARA GRASIELA ALVES1; MARINALDO FERREIRA PINTO2; ANA PAULA ALVES BARRETO DAMASCENO3; VANESSA DE FÁTIMA GRAH3 E TARLEI ARRIEL BOTREL4 1Doutorando em Eng. de Sistemas Agrícolas, bolsista do CNPq, Escola Superior de Agricultura “Luiz de Queiroz”, Universidade de São Paulo, dinara@usp.br 2Doutor, funcionário do Departamento de Biossistemas, Escola Superior de Agricultura “Luiz de Queiroz”, Universidade de São Paulo, marinaldopinto@usp.br 3Doutorando, Escola Superior de Agricultura “Luiz de Queiroz”, Universidade de São Paulo, pauladamasceno@usp.br, vanessagrah@usp.br 4Prof. Doutor, Escola Superior de Agricultura “Luiz de Queiroz”, Universidade de São Paulo, tabotrel@usp.br 1 ABSTRACT There are several sources of power for driving motors, but electric motors and diesel engines are most commonly used in irrigation in Brazil. However, the use of diesel engines typically occurs in areas without electricity nearby, making it generally viable. Another option is to use sunlight as an alternate energy source, but this system is not widely used due to its high initial cost, and its use is mainly limited to places where there is no electricity. In view of this, the economic analysis of water pumping systems in agriculture is critical, because the capital employed is often high and the annual costs may or may not enable the agricultural activities that use them. Therefore, the objective of this study was to compare water pumping costs using an electric motor powered by solar energy and a diesel motor in a drip irrigation system with microtubes. It was considered an area of 1 ha, planted with vegetable crops whose water demand is 5.6 mm, under drip irrigation. This area was divided into eight parts, each of them being irrigated for 1 hour. The lift system for pumping water that used solar energy had lower total cost and higher initial investment cost. The lift system with solar energy is more economically viable when compared with the system running on diesel. The pumping cost was the deciding factor in the analysis of the costs of water pumping systems. Keywords: Microirrigation, microtube, economic analysis